Therapy Changes During Pemphigus Management: A Retrospective Analysis - Scarpone, Roberta; Francuzik, Wojciech; Worm, Margitta; Heine, Guido (Frontiers in Medicine, 2020)
Pemphigus diseases are rare and the treatment response differs between patients. Several therapy changes are often required to achieve both disease control and to avoid unwanted side effects. We aimed to analyze the treatment courses of pemphigus patients and the clinical responses regarding ther-apy changes. Pemphigus patients in our center were retrospectively examined according to the medica-tion and dosage, disease activity, reason for treatment changes, and autoantibody concentrations. Thera-py changes due to insufficient therapeutic effects or side effects were analyzed. 77 pemphigus patients with repeated consultations were identified (81% pemphigus vulgaris, 19% pemphigus foliaceus). Dis-ease control was achieved with an average of 4 different therapy regimens (range 1-18 changes). Dis-ease control was reached in 66 patients (86%; score “almost clear” or “clear”), after an average of 2 years of treatment (range 0-11 years). 22 patients (29%) with refractory disease received rituximab, of which 19 (86%) subsequently achieved remission. Anti-desmoglein-1 and -3 concentrations correlated with disease severity, but not with the number of treatment changes. The identification of an effective and safe therapy for the individual pemphigus patient is a challenge and often requires time, reflected by a high number of therapy changes. Predictive parameters are warranted to directly identify the safest and most efficient treatment regimen for an individual patient.